Predicting the Impact of Intellectual Capital Management on the Performance of SMEs in Electronics Industry in Kuching, Sarawak - Khalique, Muhammad; Md Isa, Abu Hassan; Nassir bin Shaari, Jamal Abdul (EBSCOHOST, 2013)
Intellectual Capital (IC) has secured an overwhelming response in the research domain in a knowledgebased economy. However, in Malaysia, previous studies rarely examined the role of IC in Small and Medium Enterprises (SMEs). In addition, most studies neglect the SMEs operating in Kuching, Sarawak. The main crux of this paper is to explore the role of IC management as an integral element of electronics organizations in Kuching, Sarawak, Malaysia. IC management plays a critical role for the development and sustenance of SMEs. In the beginning of the 21st century, it was observed that the IC management attained significant attention from academicians, researchers and practitioners. Therefore, it is indispensible to examine the role of IC in SMEs. This study uses survey method to examine the effects of IC on the performance of SMEs. A total of 130 participants were involved in this study. The findings were based on the empirical data from electronics SMEs operating in the service sector , Kuching, Sarawak, and generated by Pearson correlation method. Results reveal that Human Capital (HC) has the strongest relationship with Organizational Performance, followed by Spiritual Capital (SC), Technological Capital (TC) and Customer Capital (CC).